Ethnobotanical Study of Zingiberaceae to Reinforce Plant Taxonomy Concepts through Field Practice - Novinovrita M; Indah Kencanawati (Faculty of Tarbiyah and Teacher Training UIN Jurai Siwo, Lampung, 2025)
Botany plays a crucial role in shaping students’ understanding of biodiversity and its relevance to daily life. However, theoretical approaches often create a disconnect between scientific knowledge and its real-world application. This study aimed to assess the effectiveness of practice-based ethnobotany learning in enhancing students’ biological understanding, cultural awareness, and critical thinking skills. Using a qualitative descriptive approach combined with experiential learning methods, data were collected through direct observation of Zingiberaceae species, semi-structured interviews with local communities on plant uses, scientific literature reviews on pharmacological benefits, and visual documentation. The findings revealed that this approach strengthened students’ grasp of plant taxonomy, conservation values, and local wisdom. Students successfully identified various species such as Curcuma domestica, Zingiber officinale, and others, along with their traditional health and environmental benefits. Additionally, the learning process significantly improved students' critical thinking and self-efficacy in applying acquired knowledge. The results emphasize that real-world experiences enhance theoretical understanding and foster ecological awareness. This study suggests that ethnobotany education grounded in field practice should be more widely implemented in higher education, especially in biology and environmental science. Integrating this approach supports not only academic achievement but also character development, cultural preservation, and sustainable development in response to 21st-century educational challenges.